Hubungan Komitmen Profesi, Sosialisasi Antisipatif dan Pertimbangan Moral dengan Whistleblowing - Yusti Pujisari (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2013)
This study aims to test empiracally the relationship commitment of the professin, anticipatory socialization and moral considerations against whistleblowing. This study tested the acoounting students in Yogyakarta who have been through auditing. The relusts showed that the influence of professional commitment, the inluence of anticipatory socializaation, and the influence of moral considerations against whistleblowing is not supported empirically.